Sistem Monitoring Dan Notifikasi Suhu Dan Kelembaban Udara Pada Jamur Tiram Menggunakan ESP8266 Dengan Platform IOT - Sri Ayuni; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Internet of Things (IoT) is a concept to exchange data through the internet with objects that can be controlled remotely. Oyster mushrooms are white mushrooms that have a curved shape and have nutritional value that is rich in protein, vitamins, carbohydrates andminerals. Problems that occur in Omah Cendawan often experience crop failure, caused due to lack of care such as maintaining temperature, humidity and pests that attack oyster mushrooms.This system was designed to help oyster mushroom farmers to find out the temperature and humidity of the oyster mushroom. The tools used in this study consisted of ESP8266, DHT22,LCD, power bank. DHT22 is used to detect temperature and humidity of the air by sending notifications to farmers through the blynk application. The thingspeak.com is used to viewmonitoring data from sensors. The test results show, the time needed to be able to send notifications blynk about 1-3 seconds, while the time needed to send and receive data to thingspeak.com about 30 minutes. This time can be affected by internet connection.Keywords: Internet of Things, Blynk, Thingspeak, Notification, Monitoring